Increasing skeletal muscle carnitine content in older individuals increases whole‐body fat oxidation during moderate‐intensity exercise. Issue 2 (19th January 2021) - Chee, Carolyn; Shannon, Chris E.; Burns, Aisling; Selby, Anna L.; Wilkinson, Daniel; Smith, Kenneth; Greenhaff, Paul L.; Stephens, Francis B.
Abstract: Intramyocellular lipid (IMCL) utilization is impaired in older individuals, and IMCL accumulation is associated with insulin resistance. We hypothesized that increasing muscle total carnitine content in older men would increase fat oxidation and IMCL utilization during exercise, and improve insulin sensitivity. Fourteen healthy older men (69 ± 1 year, BMI 26.5 ± 0.8 kg/m 2 ) performed 1 h of cycling at 50% VO2 max and, on a separate occasion, underwent a 60 mU/m 2 /min euglycaemic hyperinsulinaemic clamp before and after 25 weeks of daily ingestion of a 220 ml insulinogenic beverage (44.4 g carbohydrate, 13.8 g protein) containing 4.5 g placebo ( n = 7) or L‐carnitine L‐tartrate ( n = 7). During supplementation, participants performed twice‐weekly cycling for 1 h at 50% VO2 max. Placebo ingestion had no effect on muscle carnitine content or total fat oxidation during exercise at 50% VO2 max. L‐carnitine supplementation resulted in a 20% increase in muscle total carnitine content (20.1 ± 1.2 to 23.9 ± 1.7 mmol/kg/dm; p < 0.01) and a 20% increase in total fat oxidation (181.1 ± 15.0 to 220.4 ± 19.6 J/kg lbm/min; p < 0.01), predominantly due to increased IMCL utilization. These changes were associated with increased expression of genes involved in fat metabolism (ACAT1, DGKD & PLIN2; p < 0.05). There was no change in resting insulin‐stimulated whole‐body or skeletal muscle glucose disposal after supplementation. This is the first study to demonstrate that a carnitine‐mediated increase in fat oxidation is achievable in older individuals. This warrants further investigation given reduced lipid turnover is associated with poor metabolic health in older adults. Abstract : High Intramyocellular lipid (IMCL) content in older individuals, likely due to reduced fat oxidation, is associated with insulin resistance. The present study demonstrated that increasing muscle carnitine content in healthy older males resulted in a 20% increase in fat oxidation during exercise, likely due to an increase in IMCL utilization. This was supported by changes in expression of genes associated with IMCL turnover and oxidation, but no improvement in insulin sensitivity was observed.